Design of a parallel cluster-randomized trial assessing the impact of a demand-side sanitation and hygiene intervention on sustained behavior change and mental well-being in rural and peri-urban Amhara, Ethiopia: Andilaye study protocol - Maryann G. Delea (BMC Public Health, 2019)
Abstract Background Unimproved water, sanitation, and hygiene (WASH) behaviors are key drivers of infectious disease transmission and influencers of mental well-being. While WASH is seen as a critical enabler of health, important knowledge gaps related to the content and delivery of effective, holistic WASH programming exist. Corresponding impacts of WASH on mental well-being are also underexplored. There is a need for more robust implementation research that yields information regarding whether and how community-based, demand-side interventions facilitate progressive and sustained adoption of improved sanitation and hygiene behaviors and downstream health impacts. The purpose of this protocol is to detail the rationale and design of a cluster-randomized trial evaluating the impact of a demand-side sanitation and hygiene intervention on sustained behavior change and mental well-being in rural and peri-urban Amhara, Ethiopia. Methods Together with partners, we developed a theoretically-informed, evidence-based behavioral intervention called Andilaye. We randomly selected and assigned 50 sub-districts (kebeles) from three purposively selected districts (woredas); half to receive the Andilaye intervention, and half the standard of care sanitation and hygiene programming (i.e., community-led total sanitation and hygiene [CLTSH]). During baseline, midline, and endline, we will collect data on an array of behavioral factors, potential moderators (e.g., water and sanitation insecurity, collective efficacy), and our primary study outcomes: sanitation and hygiene behaviors and mental well-being. We will perform a process evaluation to assess intervention fidelity and related attributes. Discussion While CLTSH has fostered sanitation and hygiene improvements in Ethiopia, evidence of behavioral slippage, or regression to unimproved practices in communities previously declared open defecation free exists. Other limitations of CLTSH, such as its focus on disgust, poor triggering, and over-saturation of Health Extension Workers have been documented. We employed rigorous formative research and practically applied social and behavioral theory to develop Andilaye, a scalable intervention designed to address these issues and complement existing service delivery within Ethiopia’s Health Extension Program. Evidence from this trial may help address knowledge gaps related to scalable alternatives to CLTSH and inform sanitation and hygiene programming and policy in Ethiopia and beyond. Trial registration This trial was registered with clinicaltrials.gov (NCT03075436) on March 9, 2017.